A Study Of Bioconversion Method For Milk Waste Treatment Using Black Soldier Fly Larvae - Vennalia Rahmawati Sinaga; Yunita Ismail Masjud (Fakultas Teknik, 2023)
Milk waste can be managed by the composting method with the help of Black Soldier Fly larvae. The bioconversion process is a process of decomposing organic waste through a composting process using natural microorganisms to produce products in the form of humus and black soldier fly larvae. This study aims to find out how the variation in the composition of the maggot feed media on wet weight, dry weight, and black soldier fly larvae reduction rate on maggot protein quality meets the general standard of maggot crude protein. content in the range of 30-50%. The method used is a non-factorial Completely Randomized Design with follow-up tests Analysis of Variance (ANOVA), Least Significance Different (LSD) test and T-test. The highest average dry weight was obtained from treatments B and C, namely treatment B 266.5 g and treatment C 213.65%. The highest level of waste reduction was obtained from treatment C with a waste reduction index of 4.96%. Then on the results of the T test the average protein content obtained in treatment C with an average protein content of 29.59% meets the quality standard for general protein content for alpha levels (α = 0.05).